Penafsiran Imam Asy-Syaukani Tentang Mukāʾan Wa Tasdiyah (Analisis Semantik Toshihiko Izutsu) - Syawalia, Zahiyah Tika; Hakiki, Kiki Muhamad; Masruchin, Masruchin (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2025)
This study examines the meaning of "mukāʾan wa tasdiyah" in the tafsir of Fathul Qadir by Imam Asy-Syaukani using Toshihiko Izutsu's semantic approach. he problem raised in this study is to explain in more depth the meaning of the word "mukāʾan wa tasdiyah" in the context of Asy-Syaukani's interpretation and to look at it from Toshihiko Izutsu's semantic analysis. The word "mukāʾan wa tasdiyah" in QS. Al-Anfal verse 35 describes the custom of polytheists who perform rituals around the Kaaba with whistling and clapping as a form of mockery of worship. The Qur'an clearly criticizes the practice as a worship that has no value of submission to Allah and is only a form of play without spiritual meaning. The method used in this study is a qualitative method (library research) and uses Toshihiko Izutsu's semantic analysis. The results of the study, through Izutsu's semantic analysis, it was found that the meaning of "mukāʾan wa tasdiyah" has shifted from neutral to negative nuances in the Qur'anic value system. The word "mukāʾan" means whistling, while "tasdiyah" means clapping hands, which in this context is used by polytheists to disrupt worship. Imam Asy-Syaukani in his commentary explained that this action not only shows an insult to Islamic worship, but also as a real effort to prevent Muslims from worshiping solemnly. Thus, this study highlights how Imam Asy-Syaukani interprets worship behavior carried out without submission to Allah and is strengthened by Toshihiko Izutsu's semantic analysis to obtain a deeper explanation and meaning.